Efeitos da frequência de conhecimento de resultados (cr) na aquisição de uma habilidade motora em adultos e crianças - Márcia Salomão de Castro (2016)
The frequency in providing results of knowledge (KR) has been seen as one of the factors favoring the learning of motor skills. This assumption has been taken taking into account the results of studies in adults. However, these would be the same findings when the sample was made up of children? Which have among their main differences with adults the level of development. From this question, the objective of this study was to investigate the effect of knowledge of results frequency (KR) in the acquisition of motor skills in children and adults. The study consisted of two experiments. In one experiment investigated the effects of KR frequency in the acquisition of motor skills in adults. While, in the second experiment the objective was to investigate the effects of KR frequency in the acquisition of motor skills in children. Both experiments used a manual transport task with target date. A tennis ball transported in a predetermined sequence and target time. The instrument used was device Reaction Time Control and Movement (CTRM). The procedures adopted and experimental design were the same for both experiments trying to reduce interference in the results by number of attempts, breaks, experimental phase of the effect of KR frequency. Each experiment had the participation 30 volunteers of both sexes and inexperienced in the job. The volunteers were divided into three groups (n = 10) with KR frequency, 100%, 66% and 33%. The experiments consisted of the acquisition phase (30 trials with specific KR per group) and retention test (10 attempts without KR). The results of experiment one (adults) determined that the groups often 66% and 33% KR showed better performance in accuracy compared to the group 100% KR. However, the experiment two (children) there were no differences between the groups with frequencies of 100%, 66% and 33% KR. These results seem related to the different level of development of children, particularly, with regard to information processing.